Hepatocellular carcinoma: Where there is unmet need. Issue 8 (25th June 2015) - Bupathi, Manojkumar; Kaseb, Ahmed; Meric-Bernstam, Funda; Naing, Aung
Abstract : Hepatocellular carcinoma (HCC) is a complex and heterogeneous tumor most commonly associated with underlying chronic liver disease, especially hepatitis. It is a growing problem in the United States and worldwide. There are two potential ways to prevent HCC. Primary prevention which is based on vaccination or secondary prevention involving agents that slow down carcinogenesis. Several pathways have been thought to play a role in the development of HCC; specifically, those involving vascular endothelial growth factor (VEGF)‐mediated angiogenesis, WNT, phosphatidylinositol 3‐kinase (PI3K)/AKT/mammalian target of rapamycin (mTOR), AMP‐activated protein kinase (AMPK), and c‐MET. Currently, there are only a limited number of drugs which have been proven as effective treatment options for HCC and several clinical trials are testing drugs which target aberrations in the pathways mentioned above. In this review, we discuss currently approved therapies, monotherapies and combination therapy for the treatment of HCC. Highlights: Limited drugs of proven efficacy are available for treatment of patients with HCC. Cross‐talk between signaling pathways hampers the efficacy of targeted agents. Pre‐ and post‐treatment biopsy may shed light on pathways of resistance in HCC. Development of combination therapies may help to overcome resistance in HCC.